Toward a Unified Injection Model of Short-lived Radioisotopes in N-body Simulations of Star-forming Regions - Joseph W. Eatson; Richard J. Parker; Tim Lichtenberg (The Astrophysical Journal)
Recent research provides compelling evidence that the decay of short-lived radioisotopes (SLRs), such as ^26 Al, provided the bulk of energy for heating and desiccation of volatile-rich planetesimals in the early solar system. However, it remains unclear whether the early solar system was highly enriched relative to other planetary systems with similar formation characteristics. While the solar system possesses an elevated level of SLR enrichment compared to the interstellar medium, determining SLR enrichment of individual protoplanetary disks observationally has not been performed and is markedly more difficult. We use N -body simulations to estimate enrichment of SLRs in star-forming regions through two likely important SLR sources: stellar winds from massive stars and supernovae (SNae). We vary the number of stars and the radii of the star-forming regions and implement two models of stellar-wind SLR propagation for the radioisotopes ^26 Al and ^60 Fe. We find that for ^26 Al enrichment the solar system is at the upper end of the expected distribution, while for the more SNae-dependent isotope ^60 Fe we find that the solar system is comparatively very highly enriched. Furthermore, combined with our previous research, these results suggest that the statistical role of ^26 Al-driven desiccation on exoplanet bulk composition may be underestimated in typical interpretations of the low-mass exoplanet census, and that ^60 Fe is even less influential as a source of heating than previously assumed.